An 18-Year-Old Male Patient Presenting with Splenic Cyst and a History of Kidney Transplantation - Rahimzadeh, Nahid; Mousavi, Hamzeh; memarian, Mahan; Riahi, Aina (Journal of Pediatric Nephrology, 2021)
The spleen is the most commonly injured solid organ in blunt abdominal trauma and contributes to mortality and morbidity. Epidermoid splenic cysts are an example of primary congenital cysts that contain an epithelial lining, unlike secondary cysts that are collection of fibrous tissue. An 18-year-old male presented with acute left upper abdominal pain, feeling of fullness, and dyspepsia since 10 days ago. His past medical history was positive for renal transplantation from deceased donor five years prior to presentation. Physical examination revealed normal findings except a palpable soft mass measuring 15x20 cm in the left upper quadrant (LUQ).